Paleomagnetism and Plate Tectonics. - Francheteau,Jean (1970)
Paleomagnetism and plate tectonics are combined in a new procedure for producing paleogeographic reconstructions of the evolution of present day world geography from proto-continents. For each geologic epoch, the continents are first subjected to rotations relative to each other from the data of plate tectonics, then another rotation is carried out with respect to the Earth's spin axis by swinging the virtual paleomagnetic poles to the present north pole in a single rotation. The new method checks Bullard's reconstruction of the continents surrounding the Atlantic Ocean which was accomplished by computer fitting of their continental shelves. (Author)